Psychological Features Of Parent-Child Relationships And Their Impact On The Socialization Of Adolescents With Behavior Deviations (Eurasian Journal of Humanities and Social Sciences, 2025)
This article discusses the relationship between inappropriate behavior of adolescents and child-parent relationships in their socialization.